Comorbidity and sociodemographic characteristics of adult autism spectrum disorder and attention deficit hyperactivity disorder: epidemiological investigation in the World Mental Health Japan 2nd Survey. (2nd January 2021) - Umeda, Maki; Shimoda, Haruki; Miyamoto, Karin; Ishikawa, Hanako; Tachimori, Hisateru; Takeshima, Tadashi; Kawakami, Norito
Abstract : Objectives: The present study aims to examine sociodemographic correlates and comorbid mental disorders among adult with autism spectrum disorders (ASD) and attention deficit hyperactivity disorders (ADHD) using the national representative data of Japan. Methods: Analysis was conducted on the cross-sectional data derived from the World Mental Health Japan Survey 2, whose participants were community residents aged 20–75 years old. Multiple logistic regression was conducted on the data of those who were assessed for adult ASD ( N = 2227) and ADHD ( N = 2297). The association of adult ASD/ADHD with sociodemographics, mood disorders, anxiety disorders, substance use disorders, suicide ideation, hikikomori (social withdrawal), and internet addiction was examined, adjusting for sex and age. Gender difference in the association was also assessed based on the interaction terms of sex. Results: None of the sociodemographics characteristics were significantly associated with adult ASD/ADHD. ADHD had increased risks for a variety of mental disorders, having the highest odds ratios for social phobia. However, a significant positive association was limited to social phobia and to drug abuse and dependence among those with adult ASD. Hikikomori and internet addiction were positively associated with ASD/ADHD, while suicide ideation was only associated with ADHD. Women with ADHD were more likely to have any one of mental disorders, as well as alcohol abuse and dependence, compared to men with ADHD. Conclusions: Adults with ASD/ADHD in Japan had increased mental health needs. The specific needs of women with ADHD should be also considered in future clinical work and research.